Pengembangan Scaffolding pada Discovery Learning dalam Meningkatkan Kemampuan Pemecahan Masalah - Munawir Nursyahrobby; M. Rusdi; Diah Riski Gusti (Journal on Education, 2023)
Scaffolding is a help given to students to learn and solve problems. This study aims to describe scaffolding development procedures in discovery learning to improve problem-solving skills. The research method used is a research procedure to develop a learning design model with the type F2-O1+O2-S1+S5+S6-A3. The data was collected using the Delphi technique and analyzed using qualitative data analysis methods. Based on the validation results by experts and practitioners, the product is declared suitable for learning. The results of small group trials show that the product effectively improves students' problem-solving abilities in learning activities. Applying scaffolding products in discovery learning can improve students' problem-solving skills at reaction rates.